A preliminary study into the impact of using three-dimensional models in forensic anthropology learning and teaching. Issue 6 (November 2022) - Craik, Kathryn; Collings, Amber J.
Highlights: Using 3D digital models was not detrimental to the comprehension of students. 3D digital models were positively received by students. Students reported 3D models improved their confidence. Students responded most positively to the use of 3D models when used in conjunction with 2D images. 3D digital models are recommended as supplements to and not replacements of traditional bone labs. Abstract: Forensic anthropology has traditionally relied on two-dimensional (2D) images, such as photographs and sketches, to perform analyses, and disseminate findings. However, as 3D imaging technology advances, it has become more widely implemented into forensic anthropology analysis and practice. Teaching and learning in forensic anthropology still often relies on 2D images, but increasingly three-dimensional (3D) models are available to be used by students training in anatomy and osteology. Additionally, 3D models have been found to be beneficial to comprehension in other contexts within forensic anthropology, such as in the courtroom. The use of these models in the teaching of forensic anthropology is not yet widely implemented and more importantly, the impact on learning is not yet understood. The use of 3D imaging and visualisation in other educational contexts has seen positive results, for example in medical training. To explore this further, a study was conducted using an online activity to compare the comprehension scores of students educated using 2D textbook style images or 3D models on Sketchfab. The results showed that the use of 3D images was not detrimental to comprehension. Students using the 3D models were more consistent in their performance and reported an increase in confidence regardless of prior experience. The results of this study are of particular importance when distance learning due to the COVID-19 pandemic which means that students cannot always learn in a laboratory environment.